ANALISIS NETWORK PLANNING DENGAN CRITICAL PATH METHOD (CPM) DALAM USAHA EFISIENSI WAKTU PADA PRODUKSI PRECAST DI PT XYZ - Safa’at, Safa’at (STIE Mahardhika, 2018)
PT. XYZ is a company engaged in the field of readymix and precast concrete. This research is aimed to evaluate and accelerate the implementation time of the work and the cost with critical path method (CPM), it is expected that the work execution time will be faster and more efficient. The method used is to interview the employees in accordance with their fields and collect the necessary documents, from the data is evaluated and then performed improvement measures to speed up the work and cost efficiency. From the result of the research, it can be concluded that with the application of critical path method (CPM), the execution time of the work can be accelerated and more efficient.